Holocene heathland development in temperate oceanic Southern Hemisphere: Key drivers in a global context. (9th February 2021) - Adeleye, Matthew Adesanya; Haberle, Simon Graeme; Harris, Stephen; Hopf, Felicitas Viktoria‐Louise; Connor, Simon; Stevenson, Janelle
Abstract: Aim: Understanding long‐term heathland development is key in mitigating their current attrition globally. However, such knowledge is limited in Australia and the wider Southern Hemisphere. We aim to identify potential climatic and environmental drivers of Holocene heathland development in temperate‐oceanic Australia (Bass Strait), and also assess the applicability of Iversen's conceptual model of interglacial vegetation development to the area. Location: Bass Strait, southeast Australia. Taxon: Monotoca, Epacris, Sprengelia and Restionaceae. Methods: We used multiple sedimentary pollen and charcoal records from truwana/Cape Barren Island (CBI) in Bass Strait to reconstruct vegetation and fire history. We also used rarefaction analysis on pollen records to estimate floristic richness for all sites, and magnetic susceptibility and organic content were derived for two of the four sites as proxies for local sedimentary changes. Reconstructed vegetation and fire histories were then compared to independent records of climate and sea‐level change in temperate Australia, using a Detrended Correspondence Analysis ordination, to identify major drivers of heathland development. Results: Major heathland expansion occurred on truwana/CBI between the early and mid‐Holocene in response to sea‐level rise, high effective precipitation, reduced seasonality and increased Indigenous burning. Increasing seasonality, low effective precipitation, El Niño‐Southern Oscillation intensification, stable sea level, and decreased fire activity drove the expansion of scrub and woodland at the expense of heathland in the late Holocene. The overall vegetation development on truwana/CBI fits poorly with the classic Iversen conceptual model of interglacial vegetation development in the Northern Hemisphere, due to the significant role of interglacial sea‐level rise on truwana/CBI. Therefore, a modified model, which takes into account the role of sea‐level change, is proposed for Southern Hemisphere‐temperate‐oceanic settings. Main conclusions: Heathland developments in both hemispheres reflect some level of homogeneity, considering the roles of increased Indigenous burning and reduced seasonality in both hemispheres. Frequent, controlled burning strategies are recommended to maintain heathland on truwana/CBI.